Stress-induced formation of TCP phases during high temperature low cycle fatigue loading of the single-crystal Ni-base superalloy ERBO/1. (15th April 2019) - Meid, Carla; Eggeler, Mario; Watermeyer, Philipp; Kostka, Aleksander; Hammerschmidt, Thomas; Drautz, Ralf; Eggeler, Gunther; Bartsch, Marion
Abstract: The microstructural evolution in the single crystal Ni-base superalloy ERBO/1 (CMSX 4 type) is investigated after load controlled low cycle fatigue (LCF) at 950 °C (load-ratio: 0.6, tensile stress range: 420–740 MPa, test frequency: 0.25 Hz, fatigue rupture life: about 1000 - 3000 cycles). Bulk topologically close packed (TCP) phase particles precipitated and were analyzed by three-dimensional focus ion beam slice and view imaging and analytical transmission electron microscopy. The particles did not precipitate homogenously but at locations with enhanced levels of local stresses/strains, such as isolated γ-channels subjected to cross channel stresses, shear bands and in front of micro cracks. The influence of stress/strain is furthermore apparent in the spatial arrangement and the shape of the TCP phase particles. Only μ-phase TCP particles were found by electron diffraction. Results of a structure-map analysis suggest that most of these TCP particles observed after LCF testing would not precipitate in thermodynamic equilibrium. In order to rationalize this effect, the atomic volume was analyzed that transition-metal (TM) elements take in unary fcc and in unary μ-phase crystal structures and found that all TM elements except Zr and V take a larger volume in a unary μ phase than in a unary fcc phase. This trend is in line with the observed localized precipitation of TCP phases that are rich in Ni and other late TM elements. The experimental and theoretical findings suggest consistently that formation of TCP particles in LCF tests is considerably influenced by the local tensile stress/strain states. Graphical abstract: Image 1